Co-management and social equity at Silaka and Hluleka Nature Reserves, South Africa - Mtshintsho, Anda (Rhodes University, Faculty of Science, Department of Environmental Science)
Co-management of protected areas (PAs) is a desired conservation approach aimed at balancing ecological goals and livelihood needs. Central to co-management are issues related to power sharing, responsibilities and benefit sharing. However, there still remains a dominance of an ecological emphasis in PA management, with studies focusing more on 'objective' biodiversity indicators for measuring the effectiveness of protected areas. However, focusing only on ecological indicators addresses a narrow perspective of achieving ecological integrity and misses social dimensions that, in some cases, might be considered more important than technical considerations. Particularly, in contexts with a history of socio-physical displacement of Indigenous people and local communities (IPLC), the social dimensions of wellbeing are complexly embedded into the economic and ecological dimensions, such that ignoring these linkages might jeopardise the success of protected areas. Thus, the aim of this study was to examine the state of research and conceptual advances on social indicators of conservation success in co-managed PAs and stakeholder views and perceptions on socially just conservation in co-managed protected areas in Silaka and Hluleka Nature Reserves, South Africa. To achieve this, a scoping review, semi-structured interviews and futures workshops (using the three horizons framework) were conducted. Findings from the scoping review (chapter 2) revealed that much of the reported social monitoring indicators still rely on quantifiable metrics (i.e., economic benefits) and less on subjective and relational metrics (i.e., qualitative strength of social networks and perceptions). Unsurprisingly, many of the reviewed case studies revealed the use of participation as an indicator of evaluating co-management success. Further, the interviews and futures workshop results in chapter 3 showed that the non-accrual of key co-management expectations such as the employment of local people, benefit-sharing (material or otherwise), participation in decision-making and community development has led to heightened conflicts between the reserve management agency and local people. Consequently, the respondents did not value the co-management arrangements, citing unfulfilled promises. Broadly, the findings of this study emphasise the need for collective and collaborative efforts in developing indicators that are not only socially just but those that are context dependent and sensitive.
Keywords: Natural resources Co-management; Social equity; Benefit sharing; Protected areas Public use -- South Africa -- Eastern Cape; Indigenous peoples Attitudes